What Does It Mean To Be a Family Man in a Matrilineal Society? Masculinity and Women’s Empowerment in Akan, Ghana - Shin, Mihye (Matrix, 2025)
The definition of ideal (hegemonic) masculinity has shifted over time and across social contexts. This study explores narratives of the lives and experiences of the Akan people in Ghana through an ethnographic lens for their changing understanding of masculinity. Akan communities are matrilineal in structure but embedded with patriarchal values. Focusing on concepts and practices of masculinity across generations within this context of matrilineal patriarchy, the research examines how people perceive changes in ideal masculinity and the relation of these evolving ideals to gendered power relations within the family and to women’s empowerment. In Akan matrilineal society, traditional fatherhood and motherhood remain central to gendered identities and as institutions that sustain patriarchy. To capture multiple social dimensions that reinforce and reproduce patriarchal power, this study adopts an intersectional framework. Through an ethnographic journey, the research provides a realistic account of masculinities and everyday life in Agogo, Ghana. While some findings may appear critical of Akan men, they reflect the lived realities of matrilineal communities as another expression of patriarchal society.